Two faces of the same coin: integrated perspectives of public and private debt on the effects of interdependence on financial stability - Rareș-Mihai NIȚU (Theoretical and Applied Economics)

(untitled)
The issue of public and private debt has become one of the central themes in global economics and finance, especially in the context of the recent economic crisis and the expansion of financial markets. This paper brings together the findings of cerebral studies that explore the combined impact of public and private debt on economic growth with the focus on their interdependence as well as the implications for macroeconomic policies. Paper highlights how these types of debt influence each other and contribute to the financial stability or instability of both developed and emerging economies. Over the past decades, debt accumulation has become a key driver for economic development supporting investment in infrastructure and innovation. However these benefits come with significant risk, particularly when the level of indebtedness exceeds certain critical thresholds. Public debt is generally used to finance long-term projects and stimulate the economy during recessions, and private debt which contributes to consumption and private sector development are not easily isolated from one another. These two forms of debt interact in ways that can generate both positive synergies and amplify the negative effects. This paper brings together the conclusions of several studies that explore the combined impact of public and private debt on economic growth focusing on their interdependence and the implications for macroeconomic policies. Throughout the analysis of various perspectives ranging from critical debt thresholds to spillover effects between regions, the paper aims to provide the number of how that can become a systemic risk factor. Moreover, it explores the relationship between sovereign debt and the financial sector which can amplify vulnerabilities during crisis periods and presents the policies needed to manage these risks.